Digital transformation in human resources management and its impact on the performance of enterprises - Yu. P. Balabanova; A. V. Lukyanova; E. Yu. Shatskaya (Вестник Северо-Кавказского федерального университета, 2024)
Introduction. The article explores the impact of digital transformation on the quality and efficiency of personnel management in an organization, identifying key directions and practical outcomes using the principles of quality management as defined by the fundamental provisions of the GOST R ISO 9000-2015 standard. The role of digital technologies in motivating employee engagement, optimizing human resources management, and supporting a factor-based process approach is emphasized.Goal. Using the successful implementation of digital strategies in an organization as an example, measurable results and key performance indicators are analyzed.Materials and methods. The theoretical and methodological basis of the study was the scientific works of leading domestic and foreign scientists in the field under study. To implement the research objectives, general scientific research methods were used: the method of theoretical generalization, synthesis and analysis, comparative analysis.Results and discussion. In the highly uncertain, ever-changing landscape of modern business, the role of digital transformation in HRM stands out as a key factor changing organizational structures and strategies to meet the needs of all stakeholders. The increasing complexity of global markets, rapid technological change and demands for increased operational efficiency have created a need for a paradigm shift in HR management.Conclusion. Globally, companies are focusing on the implementation of automation, artificial intelligence and data analytics to optimize operations and improve decisionmaking processes. Successfully integrating digital technologies into human resource management strategies redefines organizational success by highlighting the key role of human capital in the digital age. Nowadays, the synergy between digital transformation and HR management is the cornerstone of sustainable growth and organizational resilience. Digital transformation in human resource management has a profound impact on the overall efficiency and quality of work of organizations.